The impact of nutritional intervention on menstrual dysfunction in female athletes: a systematic review - Stickler, L. G.; Hoogenboom, B. J.; Brown, J. (SN Comprehensive Clinical Medicine, 2019)
Menstrual function is strongly affected by nutritional status and energy availability in female athletes, and impaired menstrual function can impact bone mineral density. Nutritional interventions have been proposed to mitigate menstrual dysfunction. The purpose of this systematic review was to assess the ability of nutritional interventions, directed at improving energy availability, to restore normal menstrual status in female athletes. PubMed, Cinahl, and SportDiscus databases were comprehensively searched. Included studies had to investigate the impact of increasing energy availability in female athletes through a nutritional intervention. The primary outcome measure of interest was menstrual status. Included studies were reviewed for methodological rigor using the American Academy of Dietetics Quality Criteria Checklist. Five studies met the inclusion criteria. Of the athletes who completed the interventions in the studies, 0-100% resumed normal menses. For those that improved, the mean length of time for return to menses ranged from 2.63 to 15.6 months. The length of the interventions (3-9 months), mean ages of the participants (17-1-22.6 years), and particular dietary intervention(s) (counseling, education, and nutritional supplementation) varied between the studies. Nutritional interventions may restore normal menses in some female athletes. Educational strategies targeted at improved eating and understanding the energy demands of sport, as well as weekly interaction with athletes should be considered.